Guidance Note for Adaptive Management - Denmark, Ministry (Government of Denmark, 2022)
This note explains what adaptive aid management is; why and when it sh ould be considered; and how it should be applied. It covers all Danish development support channels and modalities, including bilateral coun try assistance, assistance to and through civil society, the private s ector and to and through multilateral organisations. This guide has th ree chapters. Chapter 1 provides an executive overview of what adaptiv e management is. Chapter 2 goes deeper into five key operational princ iples of adaptive management. Chapter 3 details the main tenets of ada ptive management processes during the programming cycle.